2929 From Ambrose a Gumppenberg. - Desiderius Erasmus Roterodamus (Opus Epistolarum Des. Erasmi Roterodami, Vol. 10: 1532–1534, 1941)
Circulating cell-free mitochondrial DNA has recently gained attention as a sensitive biomarker of physiological stress and adaptation in athletes. Intense exercise challenges mitochondrial function and can lead to the release of circulating cell-free mitochondrial DNA into the circulation, where it acts as a mitochondrial damage-associated molecular pattern. These fragments, recognized by the innate immune system due to their bacterial-like CpG motifs, trigger inflammatory responses and reflect cellular strain. Acute bouts of high-intensity exercise, mechanical stress, or trauma are associated with sharp increases in circulating cell-free mitochondrial DNA levels, while consistent training and regular recovery help maintain lower baseline concentrations, suggesting a role in adaptive regulation. Elevated circulating cell-free mitochondrial DNA levels in athletes have been linked to impaired recovery, increased inflammatory burden, and potential overtraining, whereas controlled exercise appears to facilitate its clearance and contribute to systemic resilience. Beyond physical performance, emerging evidence suggests that circulating cell-free mitochondrial DNA is also linked to psychobiological stress, offering an insight into both the physical and mental demands placed on athletes. Monitoring circulating cell-free mitochondrial DNA dynamics alongside traditional physiological measures such as cortisol, maximal oxygen uptake, and haematological markers could therefore provide a more comprehensive assessment of training load, recovery status, and susceptibility to stress-related disorders. As sports science advances toward precision monitoring, circulating cell-free mitochondrial DNA represents a promising molecular tool for guiding individualized training programs, preventing overtraining, and safeguarding long-term athlete health.